Microtensile bond strengths and scanning electron microscopic evaluation of self-adhesive and self-etch resin cements to intact and etched enamel - Duarte, Sillas; Botta, Ana Carolina [UNESP]; Meire, Michele; Sadan, Avishai (Mosby-elsevier, 2008)
Statement of problem. The longevity of indirect adhesively cemented restorations is directly related to the bond quality of resin cements to dental tissues. Bonding to cervical enamel can generate significantly lower bond strengths than bonding to other enamel areas. The effect of enamel pretreatment on bond strengths of self-etch and self-adhesive resin cements to cervical enamel remains undetermined.Purpose. The purpose of this study was to evaluate cervical enamel bond strengths of self-adhesive, self-etch resin cements according to acid pretreatment, using a total-etch resin cement as the control.Material and methods. The proximal surfaces of 20 extracted molars were sectioned to obtain 40 enamel rectangles with an area of 8.0 x 4.0 mm. The rectangular enamel specimens were assigned to 1 of 5 enamel experimental groups: intact enamel + RelyX Unicem (UN), etched enamel + UN (UNpa), intact enamel + Multilink (ML), etched enamel + ML (MLpa), and the total-etch-based RelyX ARC (RX; control group). Standard 8.0 x 4.0 x 6.0-mm composite resin blocks (Z250) were cemented to all specimens. The bonded enamel surfaces were sectioned into sticks with a cross-section of 0.8 +/- 0.2 mm(2) and tested to failure in tension mode at a crosshead speed of 1 mm/min. The data were submitted to 1-way analysis of variance (ANOVA), followed by Tukey's HSD post hoc test (alpha=.05). Additionally, the enamel etching pattern was investigated for all experimental groups using field-emission electron microscopy.Results. Statistical analysis showed significant differences among different resin cements (P<.001) and phosphoric acid etching (P<.002). The highest mean (SD) bond strengths were obtained with UNpa (32.92 (4.23)) > RX (19.40 (9.47)). Acid etching of enamel before application of self-etch resin cement did not improve the mean bond strengths (SD) for self-etch resin cement [ML (5.38 (5.97)); MLpa (5.23 (1.1))]. Self-adhesive and self-etch resin cements yielded the lowest significant mean bond strengths (SD) when applied on intact enamel: UN (13.03 (2.82)) > ML (5.38 (5.97)). Scanning electron microscopy showed a consistent etching pattern for phosphoric acid-etched specimens. Self-etch and self-adhesive resin cements applied directly to intact enamel showed inconsistent areas of etching.Conclusions. Etching cervical enamel surfaces resulted in significantly higher bond strengths for self-adhesive resin cement. For self-etch resin cement, etching did not improve bond strength.